ANALISIS KOMODITI DOMINAN DAN PRODUKTIVITAS PURSE SEINE YANG BERBASIS DI TEMPAT PELELANGAN IKAN UJUNGBATU KABUPATEN JEPARA - Mohammad Imron; Siti Oftafia Wijayanti; Eko Sri Wiyono (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2020)
Fishing with purse seine fishing gear has been carried out by many fishermen, which are generally aimed at catching pelagic fish. Jepara District is one of the coastal areas of the North Coast of Java, located in Central Java Province. This condition makes Jepara Regency have a marine-based economic side of life which has the potential of fish resources that have been used by local fishermen for a long time. The current condition has a tendency to decline in production, which is thought to be due to overfishing. This study aims to obtain an overview of the dominant fish caught by the purse seine and to see the productivity of the purse seine. The research method used is a survey method, by conducting interviews with 20 fishermen, the head of the Ujungbatu Fish Auction Place (TPI) and his staff. The data obtained are data on catch production, composition of types of catch and other data. The results are expected to be able to provide an overview of the dominant fish catch and productivity of purse siene in the waters of Jepara District. The conclusion that can be drawn from this research is that there are three types of fish that are dominant catch, namely layang fish, mackerel and squid. During the last five years (from 2015 - 2019), production tends to experience a significant decline. Meanwhile, the productivity has also decreased as well. Based on the calculation of the productivity level according to KEPMEN KP No.61/2014, the productivity level (2019) of purse seines that land their catch at TPI Ujungbatu Jepara is 4.45, meaning that the production produced in 2019 year is 4.45 tons per vessel 1 GT used. Keywords: : Purse Seine, Dominant Comodity, Productivity, Jepara